TINGKAT KONSUMSI MAKAN DAN STATUS GIZI ANAK USIA 2-5 TAHUN PADA KELUARGA MISKIN DI DAERAH PESISIR SITUBONDO - Thohirun Thohirun; Sulistiyani Sulistiyani; Rosi Marta Wahyuningrum (Jurnal Ilmu Kesehatan Masyarakat, 2010)
This study intended to discuss the correlation between food consumption (energy, carbohydrate, protein and fat) and nutritional status of 2-5 years old children of poor family. This observational-analytical study is implemented by involving 83 samples taken by proportional random sampling. The result showed that 75% of the children were in good nutritional status. All respondents’ families had income below regional minimum income standard. Furthermore, 69.9% of mothers were elementary school graduates, and 86.8% of mothers had little knowledge of nutrition. Respondents’ consumption degree was also low; 58% suffered from energy deficit, 94% suffered from carbohydrate deficit, 67% good protein consuming, and 71% good fat consuming. The analysis showed that there was a correlation between energy and fat consumption degree and nutritional status, and there was no correlation between carbohydrate and protein consumption degree and nutritional status. Keywords: food consumption, nutritional status, poor family